2014
DOI: 10.1097/scs.0000000000000830
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Human Bone Morphogenetic Protein-2 Promote and Stabilize Hard and Soft Tissue Healing for Large Mandibular New Bone Reconstruction Defects

Abstract: Numerous autogenous bone-grafting procedures are available for the recovering of large continuity defects of the mandible. However, these surgical techniques present several limitations involving postoperative morbidity and pain. The development of new bone technique reconstruction not involving autogenous bone graft would offer new opportunities for facial bone reconstruction. This report highlights the possibility of recombinant human bone morphogenetic protein type 2 (rhBMP-2) application without concomitan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
94
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(97 citation statements)
references
References 12 publications
0
94
0
3
Order By: Relevance
“…The osteoconduction of rhBMP-2 has been widely studied in various bone healing environments, and rhBMP-2 has been shown to heal critical-sized bone defects in animal models and clinical trials [25,26]. In a recent study, rhBMP-2 was used to achieve better bone healing in distraction osteogenesis in an animal study and large mandibular reconstruction defects in clinical trials [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…The osteoconduction of rhBMP-2 has been widely studied in various bone healing environments, and rhBMP-2 has been shown to heal critical-sized bone defects in animal models and clinical trials [25,26]. In a recent study, rhBMP-2 was used to achieve better bone healing in distraction osteogenesis in an animal study and large mandibular reconstruction defects in clinical trials [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Follow-up time varied from 6 months (Chao et al, 2006;Balaji, 2009;Herford and Cicciù, 2010) to 51 months (Desai et al, 2013); bone neoformation was observed in 89.3% of the cases, whereas in the remaining 10.7% of cases little bone formation or poor healing was found. Concerning the types of graft used, in three cases the authors associated rhBMP-2 with b-tricalcium phosphate matrix (Desai et al, 2013); in five cases it was associated with allografts (Glied and Kraut et al, 2010;Cicciù et al, 2012Cicciù et al, , 2014Desai et al, 2013); three cases presented no associations (Herford and Boyne, 2008); in two cases it was associated with bovine bone xenograft (Lustosa et al, 2014); in two cases with autografts (Balaji, 2009;Herford and Cicciù, 2010); in one case with microfibrillar collagen (Carter et al, 2008); in one case with autograft, hydroxyapatite and b-tricalcium phosphate matrix (Desai et al, 2013); in one case with allograft and b-tricalcium phosphate matrix (Desai et al, 2013), in nine cases with 10 mL of demineralized bone matrix (DBM) suspended in a reverse-phase medium (DynaGraft Putty) (Clokie and S andor, 2008), and in one case with hydroxyapatite and b-tricalcium phosphate matrix (Chao et al, 2006). Dental implant rehabilitations were presented only in four studies, including the present report (Herford and Boyne, 2008;Clokie and S andor, 2008;Cicciù et al, 2012) (1).…”
Section: Discussionmentioning
confidence: 97%
“…Mandibular continuity defects due to tumor resection can lead to significant morbidity that requires reconstruction techniques (Cicciù et al, 2014) in order to reestablish patient function and aesthetics. Given that iliac crest autograft and microvascularized graft can cause further morbidity and pain, and that the resulting graft often lacks in quality and height (Herford and Cicciù, 2010), the off-label use of recombinant human bone morphogenetic protein (rhBMP) has been considered as an alternative in such cases (Lustosa et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Growth factors have played a pivotal role in modern dentistry for the regeneration of periodontal and/or bone defects caused by trauma, periodontal disease, congenital abnormalities, and tumors (Alonso et al, 2010; Behnia, Khojasteh, Soleimani, Tehranchi, & Atashi, 2012; Cicciu, Herford, Cicciu, Tandon, & Maiorana, 2014; Herford, Tandon, Stevens, Stoffella, & Cicciu, 2013; Ramseier, Rasperini, Batia, & Giannobile, 2012; Yokota et al, 2014). Examples of these include the use of platelet‐derived growth factor for periodontal and peri‐implant defects (Kaigler et al, 2011), enamel matrix derivative for periodontal intrabony defects (Miron et al, 2016), and fibroblast growth factor two for periodontal defects (Cochran et al, 2016).…”
Section: Introductionmentioning
confidence: 99%